Investigation of the Relationship Between Parents’ Primary and Secondary Capacities, and Students’ Test Anxiety and Decision Making Styles. - Ergun Turkmen (The Global Psychotherapist)
Parents are among the most important stakeholders in education and training. The primary objective of this study is to investigate the core capacities that parents have developed as a result of their environment, personal characteristics, and cultural values. The second aim is to investigate the relationship between these capacities, referred to as primary and secondary capacities, their associated attitudes and behaviors, and middle school students’ test anxiety and decision-making styles.